Pengaruh Produk Domestik Regional Bruto, Indeks Pembangunan Manusia, Jumlah Penduduk, dan Tingkat Pengangguran Terbuka Terhadap Kemiskinan di Kabupaten/Kota Provinsi Nusa Tenggara Barat Tahun 2017-2024 - Syakinah Muaddah; Iwan Harsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Poverty is a complex problem and affects many aspects of people's lives and development. Its dynamics are influenced by economic conditions, human resource levels, and different social structures in various regions, so appropriate policies are needed according to the problems faced. This study aims to analyze the effect of gross regional domestic product, human development index, population, and open unemployment rate on poverty in the regencies/cities of West Nusa Tenggara Province. This research is a quantitative study, the data used is panel data from 10 regencies/cities in West Nusa Tenggara Province in 2017-2024 and analyzed using panel data regression with the best model is the Fixed Effect Model (FEM). The results show that gross regional domestic product has a positive but insignificant effect on the poverty rate, the human development index has a negative but significant effect on poverty, population has a positive and significant effect on poverty, and the open unemployment rate has a negative but insignificant effect on poverty in the regencies/cities of West Nusa Tenggara Province.